Skimming and storage factors affect the detection of heat shock protein 70 in raw bovine milk - M.R.H. Rakib; V. Messina; J.I. Gargiulo; N.A. Lyons; I.N. Pathirana; P.C. Thomson; S.C. Garcia (JDS Communications, 2025)
Heat shock proteins (HSP) play a vital role in maintaining cellular function under elevated temperatures. Among these, heat shock protein 70 (HSP70) has recently been detected in bovine milk using competitive ELISA, highlighting its potential as a noninvasive marker of cellular stress and a tool for detecting heat stress (HS) in dairy cows. However, optimal management and storage conditions of milk samples for detection of HSP70 are yet to be determined. This study aimed to evaluate how different management and storage practices affect detection of HSP70 in milk samples. Samples were skimmed by centrifugation either before storage (SBS) or after storage (SAS), and then stored under different temperatures: (a) room temperature (T1, ∼22°C), (b) refrigerated (T2, 4°C), (c) frozen (T3, −20°C), and (d) refrigerated at 4°C with a preservative (bronopol; T4). Samples were analyzed every 2 d until d 15 (d 1, d 3, …, d 15) using a competitive ELISA system (sensitivity range 31.25–2,000 ng/mL) to detect HSP70 levels. Result showed that SBS samples had the smallest reduction in HSP70 levels on d 3 when stored at T2 or T3, with decreases of 4.4% and 7.9%, respectively. In contrast, SAS samples exhibited greater reductions (44.2% at T2 and 53.9% at T3). Samples stored at room temperature (T1) showed the greatest degradation, especially in SAS samples, whereas the use of a preservative (T4) did not consistently maintain HSP70 levels in either SBS or SAS samples. The HSP70 detection showed lower variability during early storage (d 1–3) across all treatments, with SBS samples demonstrating greater stability than SAS; however, variability significantly increased by d 9 in both sample types. An apparent increase in HSP70 levels was observed from d 11 to 15 in both SBS and SAS, suggesting the influence of protein stability and interactions affecting ELISA reactivity, where further research is required. Overall, samples stored as skim milk until d 3 at 4°C or −20°C preserved HSP70 levels more effectively than whole milk, with room temperature storage being the least favorable. This pioneering study explored how sample storage and management affect HSP70 detection, providing practical guidelines for farmers and processors to preserve milk sample integrity for assessment of HSP70 as indicator of cellular stress and, potentially, HS.